Spatial distribution and influencing factors of mountainous geological disasters in southwest China: A fine-scale multi-type assessment - Shu, Bo; Chen, Yang; Amani-Beni, Majid; Zhang, Ruizhi (Frontiers in Environmental Science, 2022)
Fine-scale multi-type analysis of geological disasters is an important but insufficiently explored research field in China’s mountainous areas. Taking Meigu County (Sichuan Province, SW China), a typical disaster-prone region, as the study area, we assessed the spatial distribution of Potential Geological Disasters Spots (PGDSs) and their underlying factors. Average nearest neighbor (ANN), standard deviational ellipse (SDE), kernel density estimation (KDE), and ordinary least squares (OLS) regression were used. The findings showed that: PGDSs have a significant spatial heterogeneity and exhibited an obvious clustering characteristic. They were distributed in an elevation range of 1500-2000m, which receives an average monthly rainfall of more than 240mm, as well as in highly foliated (0.6 < Normalized Difference Vegetation Index (NDVI) < 0.8), west-facing (247.5-292.5°), and slopes of 10-20°. In addition, slope, aspect, population density, and rainfall were found as the main influencing factors. The results provide practical rural development measures with support for PGDSs avoidance and preparedness.